Fatigue life investigation of notched TC4 specimens subjected to different patterns of laser shock peening (Fracture and Structural Integrity, 2023)
The exhaustion of constructive ways for increasing the service life of parts has led to the development of new methods which can improve their material properties during operation under various loading conditions. Laser shock peening (LSP) induces compressive residual stress field which prevents fatigue crack initiation and propagation in components. Characteristics of laser impact and treatment patterns play an important role in efficiency of LSP application for improvement of fatigue properties. This work is devoted to the experimental examination of two LSP patterns to reveal the most optimal scheme from fatigue live improvement point of view. Proposed LSP pattern allowed one to increase the fatigue life of specimens with semi-circular notch by an order of magnitude. The numerical simulation of the LSP was performed to visualize the residual stress field of treated specimen after loading and to give the interpretation of the experimentally observed improvement of fatigue life.
Keywords: Laser shock peening; Fatigue life; titanium alloy TC4; Johnson-Cook plasticity model